Literasi Hak Konstitusional Anak Keluarga Tidak Mampu Dilingkungan Perkebunan Kelapa Sawit Mendapatkan Bantuan Hukum Gratis Di SMK Saintika Pekanbaru - Andrizal, Andrizal; Asnawi, Eddy; Suprayoga, Tatang; Pratama, Egy (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2025)
The problem faced by the partner in this case—some residents of Pekanbaru City—is their lack of knowledge and understanding of a government program that provides free legal aid for underprivileged families, as part of the fulfillment of their constitutional rights. The target of this community service activity is students from economically disadvantaged families living around oil palm plantation areas, whether owned by companies or individuals. These children are particularly vulnerable to legal issues arising from juvenile delinquency, such as drug abuse, brawls, and theft. The expected outcome is that the target audience will gain increased knowledge and understanding of the partner's problems. The agreed-upon solution between the proposing team and the partner is to conduct legal education through outreach activities in the form of lectures and discussions. The implementation method used is the lecture method, where the speaker delivers material and participants are given the opportunity to engage in a question-and-answer session. The detailed steps of this method include: (1) delivering the material, and (2) conducting interactive dialogues, which serve as a brainstorming session for participants to express issues, aspirations, suggestions, ideas, and solutions. The partner’s participation in this activity includes providing time and venue, as well as mobilizing the community as the target audience. The expected outcomes of this community service activity are: for the partner, an increased understanding of the right to access free legal aid; and for the proposing team, the production of a scientific article, in line with the Tri Dharma of Higher Education.